Preclinical and clinical studies of CAR-NK-cell therapies for malignancies - Li, Hongwen; Song, Wenting; Li, Zhaoming; Zhang, Mingzhi (Frontiers in Immunology, 2022)
The development of chimeric antigen receptor T (CAR-T) cell therapy, a specific type of immunotherapy, in recent decades was a fantastic breakthrough for the treatment of haematological malignancies. However, difficulties in collecting normal T cells from patients and the time cost of manufacturing CAR-T cells have limited the application of CAR-T-cell therapy. In addition, the termination of related clinical trials on universal CAR-T cell therapy has made further research more difficult. Natural killer (NK) cells have drawn great attention in recent years. Chimeric antigen receptor-NK (CAR-NK) cell therapy is a promising strategy in the treatment of malignant tumours because of its lack of potential for causing graft-versus-host disease (GVHD). In this review, we will address the advances in and achievements of CAR-NK cell therapy.